Start-Up or Scale-Up? An Approach through Economic Impact - Garcia-Tapial, Joaquín (Archīum Ateneo, 2023)
Entrepreneurship is considered to be one of the engines for transforming our world and overcoming the diverse nature of global challenges as it promotes sustained, inclusive, and sustainable economic growth, higher levels of productivity, technological innovation, full and productive employment, and decent work for all peoples (United Nations, n.d.). Over the last decade, however, this belief has been shown to be flawed given that the typical start-up is not innovative, creates only a few jobs, and generates little wealth. Policy makers are increasingly focusing as such on the so-called scale-ups, or start-ups that have experienced growth of more than 20% over the last three consecutive years. The general belief is that these companies have a big impact on the economy, especially in terms of job creation. The purpose of this paper, then, is to test whether public resources should continue to be devoted to the generation of new companies or if these should be oriented toward the promotion of high growth companies that are defined as scale-ups. To accomplish this task, we developed a multisector model based on Social Accounting Matrices (SAM) to measure this impact of start-ups and scale-ups and applied it to a regional economy (Andalusia). The results obtained suggest that while scale-ups have a greater impact on gross domestic product, productive output, and job creation compared to traditional entrepreneurial activity, this is not large enough to replace the latter.